Среда как ограничитель и стимулятор реализации туристского потенциала территории - Меркушев (Merkushev Sergey) Сергей Александрович (Географический вестник=Geographical bulletin, 2017)
Рассматриваются проблемы качества среды социально-экономических микрорайонов (округов) Пермского края, препятствующие успешной реализации туристско-рекреационного потенциала данных территорий. На основе изучения имеющегося опыта некоторых российских городов и с учетом территориальной спецификации Пермского края даются предложения по ключевым направлениям повышения качества среды, трансформации функциональной структуры округов. THE ENVIRONMENT, AS A LIMITING FACTOR AND STIMULATOR OF ITS IMPLEMENTATION OF A TOURIST TERRITORY POTENTIAL. The quality problems of socio-economic micro-regional environment (districts) ofPermregion are being disclosed in the article, they are preventing the successful realization of tourist-recreational potential in the given territories. According to the own experience of several Russian cities and with the record of territory specificity ofPermregion will give the suggestions to the key directions of how to increase the environmental quality, the transformation of the functional structures of the districts.